THE EFFECT USING DEBATE AND INTERVIEW METHOD IN IMPROVING SPEAKING SKILL STUDENT - BISMAR SIBUEA (LP2MTBM MAKARIOZ, 2021)
The Effect Using Debate and Intevrview Method In Speaking Skill Student. This Research to Analize how long the EffectUsing Debate and interview Method in improving Speaking Skill Student in English Departement Of Simalungun University.This researh focus on both Method and to looking how big the effect using both method in improving their speaking skill.theData obtained after apply both Method by divide the student be two group. The Result of this research is Debate Method andInterview Method have Effect in improving Speaking Skill Student in English Departement Of Simalungun University. BothMethode Proven could stimulate theis speaking skill by survive their opinion ,argument, in Debate Method, even in InterviewMethod , Student seems to respons the question from the Interviewer . Both Method Succes Stimulate the student to createtheir Vocabulary, Pronunciation, and their emotion in deliver their Speech. Both Method seen Challenging for them.